Perancangan dan Penguji Gasifikasi Kulit Mente dan Sekam Padi Sebagai Sumber Energi Alternatif - Harlan, Harlan; Mangalla, Lukas Kano (Teknik Mesin Universitas Halu Oleo, 2020)
The purpose of this study is to make an updraft gasification design for a mixture ofthe composition of a mixture of cashew shell and rice husk that produces an optimalgas material, the method used is to make a direct manufacture of an updraft typegasification reactor and to take temperature measurements for each of thespecified compositions. The results showed that the design of the updraftgasification device for cashew skin and rice husk functioned well, because of thegasification process carried out by the two fuels used to produce flammable gas.The best mixture composition is a mixture of 500 grams of rice husk and cashew skin 500 grams with a temperature of 450 ˚C cashew skin and rice husk that produces optimal gas. Generally, the fuel used produces in the 15-20 minutes.Keywords: Gasification reactor designer, Gasification; Alternative Energy